Marketing Analysis of Elephant Ginger in Hatinggian Village, Lumban Julu District, Toba Regency - Bancin, Arif Santosa; Harahap, Mailina; Apriyanti, Ira (Journal of Agriculture, 2024)
Ginger is a medicinal plant that is often used as a pain reliever. Demand for ginger increases along with the development of human knowledge. So to meet consumer needs, a marketing institution is needed, such as the Gajah ginger farmers in Hatinggian village. The aim of the research is to find out how the marketing channels for Gajah ginger are, to find out the marketing margin and marketing efficiency of Gajah ginger. The research sample was 22 Gajah ginger farmers, 3 collectors and 3 retailers. Data analysis uses descriptive analysis and formula equations for marketing costs, marketing margin, Farmer share, marketing efficiency. The research results show that there are two marketing channels for Gajah ginger in Hatinggian village, Lumban Julu subdistrict, namely; 1). Marketing channel I from farmers to retailers then consumers and 2). Marketing channel II from farmers to collectors then to retailers and then consumers. The market share of marketing channel I is greater than marketing channel II so that marketing channel I (6.14%) is more efficient than marketing channel II (6.89%).